Associations between baseline pain, depressive symptoms, and unpaid caregiving needs and 1-year postdischarge outcomes among seriously ill older adults admitted for trauma - Stuart Lipsitz; Christine Ritchie; Jolene Wong; Zara Cooper; Dae Hyun Kim; Tamryn Gray; Yihan Wang; Hiba Dhanani; Evan Bollens-Lund; Amanda Reich; Claire Ankuda (Trauma Surgery & Acute Care Open, 2025)
Background Many older adults with trauma have pre-existing serious illness like dementia, frailty, and organ insufficiency and are candidates for palliative care to improve outcomes and reduce downstream healthcare utilization. We hypothesize that baseline pain, depressive symptoms, and unpaid caregiving needs are associated with increased healthcare utilization in the year after trauma admission in seriously ill older adults.Methods Using the Health and Retirement Study (2008–2018) linked to Medicare claims, we identified adults aged ≥66 years admitted for trauma. We assessed pre-admission pain (none/mild vs moderate/severe), depressive symptoms (no—Center for Epidemiologic Studies Depression Scale (CES-D) <3 vs yes—CES-D ≥3) and unpaid caregiving needs (none vs any); and hospital characteristics: trauma center designation and palliative care service. The χ2 tests were used for categorical variables, and t-tests were used for continuous variables. Associations of pain, depressive symptoms, unpaid caregiving needs with healthcare utilization were tested with negative binomial and Poisson regression models.Results Among 1693 older adults with serious illness, a third (35.7%) were older than 85 years, two-thirds were female (67.5%), and almost all were White (88.7%). Before trauma, 36.4% reported moderate/severe pain, 40.2% reported depressive symptoms (CES-D >3), and 34.9% reported any amount of hours/week of unpaid caregiving needs. Adjusted analyses demonstrated that compared with those without depressive symptoms, seriously ill older adults with depressive symptoms were less likely to be alive (incidence rate ratio (IRR) 0.61, 95% CI 0.41 to 0.91), had more emergency room visits (IRR 1.62, 95% CI 1.15 to 2.27), and more hospital visits (IRR 1.48, 95% CI 1.08 to 2.03) in the year after admission. Adjusted analyses of association of pain and caregiving with healthcare utilization were not significant.Conclusions Seriously ill older trauma patients with depressive symptoms have increased healthcare utilization in the year after discharge. Palliative care interventions may improve patient outcomes and reduce postdischarge healthcare utilization.Level of evidence III.